Stability studies for yield and related component traits in castor (Ricinus communis L.): STABILITY STUDIES FOR YIELD AND RELATED COMPONENT TRAITS IN CASTOR - VERSHA SHARMA; SITA RAM KUMHAR; C TARA SATYAVATHI; MOTILAL MEHRIYA; RAMESH CHAND MEENA; RAMESH (Journal of Oilseeds Research, 2023)
Castor (Ricinus communis L.) is a non-edible oilseed crop used in the manufacturing of soaps, cosmetics and also possessing significant medicinal properties. The experiment was conducted to study G x E interactions and stability parameters in castor using three lines and ten testers, their resultant 30 hybrids and one check (GCH-8) for seed yield and related component traits under three different environments viz., kharif, 2020 at Agricultural Research Station (ARS), Mandor and kharif, 2021 at ARS, Mandor and Instructional Farm, College of Agriculture, Jodhpur. Analysis of variance showed significant difference for all the characters studied. Genotype and environment interaction was significant only for number of capsules per primary raceme, seed yield at 120 days after sowing and ricinoleic acid content. The average stability was possessed by hybrid MCP-1-1 x MP-36-17 for number of effective raceme per plant, MCP-1-1 x MP-42-17 for effective primary raceme length and 100-seed weight, and SKP-84 x MP-12-17 for number of capsules per primary raceme and 100-seed weight over all the three environments. Similarly, the hybrid MCP-1-1 x MP-35-17 showed average stability for seed yield at 120, 150, 180 and 210 days after sowing, whereas MCP-1-1 x MP-27-17 exhibited average stability for oil content, ricinoleic acid content, seed yield at 180 and 210 days after sowing. Based on overall analysis, MCP-1-1 x MP-35-17 and MCP-1-1 x MP-27-17 was found promising in arid regions of Rajasthan.